Existence of Solutions for Fractional Differential Inclusions with Separated Boundary Conditions in Banach Space - Mabrouk Bragdi; Amar Debbouche; Dumitru Baleanu (Advances in Mathematical Physics)
We discuss the existence of solutions for a class of some separated boundary differential inclusions of fractional orders 2<α<3 involving the Caputo derivative. In order to obtain necessary conditions for the existence result, we apply the fixed point technique, fractional calculus, and multivalued analysis.